2005
DOI: 10.1121/1.1886405
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of spectral and temporal cues for phoneme recognition

Abstract: Cochlear implants provide users with limited spectral and temporal information. In this study, the amount of spectral and temporal information was systematically varied through simulations of cochlear implant processors using a noise-excited vocoder. Spectral information was controlled by varying the number of channels between 1 and 16, and temporal information was controlled by varying the lowpass cutoff frequencies of the envelope extractors from 1 to 512 Hz. Consonants and vowels processed using those condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
198
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 63 publications
29
198
3
Order By: Relevance
“…Furthermore, a positive correlation between electrical DR and speech test results in noise suggests that the increase in electrical DR with rate contributed to the increase in speech test scores in noise with rate, at least for rates up to 500 pps/ch. These results were somewhat consistent with the previous findings by Pfingst and Xu (2005) which showed that subjects with larger mean dynamic range had better speech recognition in quiet and noise.…”
Section: Relationship Between Modulation Detection and Speech Perceptionsupporting
confidence: 83%
“…Furthermore, a positive correlation between electrical DR and speech test results in noise suggests that the increase in electrical DR with rate contributed to the increase in speech test scores in noise with rate, at least for rates up to 500 pps/ch. These results were somewhat consistent with the previous findings by Pfingst and Xu (2005) which showed that subjects with larger mean dynamic range had better speech recognition in quiet and noise.…”
Section: Relationship Between Modulation Detection and Speech Perceptionsupporting
confidence: 83%
“…As illustrated in Fig. 2, the lowpass cutoff frequencies required for plateau performance were almost constant in the noise conditions for consonant (16 Hz) and vowel (4 Hz) recognition as well as in quiet condition (for speech recognition in quiet, see also Shannon, 2000 andXu et al, 2005). We speculate that there are several possible explanations for the limitations of the auditory system to use more temporal information for speech recognition in noise.…”
Section: Spectral and Temporal Cues For Phoneme Recognition In Noisementioning
confidence: 96%
“…Data on how these two cues interact and affect speech recognition are needed to inform the design of speech-processing strategies that will provide better speech recognition for the cochlear implant users. We have undertaken a series of studies in an attempt to elucidate the relative importance of spectral and temporal cues and their interactions for phoneme recognition in quiet and in noise and for lexical-tone recognition (Xu et al, 2002(Xu et al, , 2005. The sections below provide a concise summary of the results of those studies and discuss the implications of the results for auditory prostheses in light of recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…The current results suggest that there is either a causal link between the ability of frequency discrimination and grammatical rule learning or a parallel development in both domains. A direct causal link could operate via the role frequency information plays in phoneme discrimination (15,30), which is a precondition for detecting long-range dependencies between phonemes. Alternatively, both pitch perception and rule Step-down analyses are given after the superordinate analysis.…”
Section: Discussionmentioning
confidence: 99%